Penguatan Hukum dan Keselamatan Kerja serta Edukasi Lingkungan dalam Pengelolaan Ekowisata Mangrove Berbasis Kearifan Lokal dan Wisata di Kelurahan Kampung Baru Kabupaten Penajam Paser Utara - Didik Hadiyatno; Kevin Gratsia Anyuanu; Mashadi Aroufallaily (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Mangrove ecosystems play a vital role in maintaining the balance of the coastal environment and providing ecological, social, and economic benefits to the surrounding community. The mangrove area in Kampung Baru Village, North Penajam Paser Regency, has significant potential for development as an environmentally-based ecotourism destination. However, the management of this area still faces several challenges, including a lack of public understanding regarding occupational safety during tourism activities, limited environmental education for visitors, and the suboptimal use of digital technology in disseminating tourism information. Therefore, this community service activity aims to strengthen occupational safety aspects, raise environmental awareness, and support the digitization of tourism information based on local wisdom. The implementation method used a participatory approach, including field observations, problem identification, socialization of occupational safety and mangrove conservation, and the installation of information boards and safety signs integrated into tourist locations. The results of the activity indicate an increase in public and tourism managers' understanding of the importance of occupational safety and environmental protection. The installation of information media and a digital tourism information system also makes it easier for visitors to obtain information about mangrove, safety regulations, and their ecological value.